The Influence of Service Quality and Company Image on Customer Satisfaction of Car Service Workshop at PT. Sun Star Prima Motor Bogor - Putri, Daffa Amalia; Samsuri; Yulianingsih (International Journal of Sustainability in Research, 2023)
This study aims to determine and analyze the quality of service and corporate image either simultaneously or partially on customer satisfaction at PT. Sun Star Prima Motor Bogor. Sampling amounted to 100 respondents who were taken by probability sampling technique with simple random sampling method. The questionnaire was tested with validity test, reliability test, and also classical assumption test. The results of these tests are valid, reliable, and can be used for regression data. The analytical method used in this research is descriptive and verification method with a quantitative approach. The results of the study show that the variables of service quality and corporate image either simultaneously or partially have a positive and significant effect on customer satisfaction at the PT. Sun Star Prima Motor Bogor. The result of testing the coefficient of determination R (square) is 45.3%, while the rest is 54.7%. The relationship between service quality and corporate image is strong with a correlation coefficient of 0.682.